2008
DOI: 10.1134/s1087659608050143
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation in melts of the ZrO2-Al2O3 system

Abstract: The morphology of the quenched and slowly crystallized samples in the ZrO 2 -Al 2 O 3 system is investigated in the composition range 25-70 wt % ZrO 2 . It is revealed that, irrespective of the cooling rate, the samples contain large baddeleyite (or corundum) crystals, eutectic mixtures, and characteristic regions of intergrown elongated baddeleyite and corundum grains with micron sizes. These regions have the same phase composition at any initial ratio between zirconium and aluminum oxides and at any cooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…For this system, the exist ence of the two phase region in melt was experimen tally determined by the data of the differential thermal analysis in work [14]. The presence of a two phase region in the melts of this system was confirmed in work [15]. The experimental results of the investiga tion carried out in conditions of gas levitation [6,7] show that there are numerous anomalies both in the physical properties of melts in the ZrO 2 -Al 2 O 3 system and in the morphology of samples crystallized from them.…”
Section: L1 L2mentioning
confidence: 72%
See 2 more Smart Citations
“…For this system, the exist ence of the two phase region in melt was experimen tally determined by the data of the differential thermal analysis in work [14]. The presence of a two phase region in the melts of this system was confirmed in work [15]. The experimental results of the investiga tion carried out in conditions of gas levitation [6,7] show that there are numerous anomalies both in the physical properties of melts in the ZrO 2 -Al 2 O 3 system and in the morphology of samples crystallized from them.…”
Section: L1 L2mentioning
confidence: 72%
“…In order to determine the possi ble relationship of the polyhedra number in the com plex we will use the obtained data for the ZrO 2 -Al 2 O 3 melts. This choice is based on the fact that there is a stable cation valence in this system, the coordination numbers of cations by oxygen for the high tempera ture modifications of oxides are reliably determined experimentally, the concentration limits of the exist ence of complexes in the melts of this system are deter mined by independent experiments [5,6,14,15]. Based on the data on the concentration dependence of surface tension one can assume that the existence region of complexes in the melts of the ZrO 2 -Al 2 O 3 system is in the range from 42 to 55% of ZrO 2 , which corresponds to a molar ratio of Al 2 O 3 : ZrO 2 = (0.37-0.50) : (0.63-0.50).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found a miscibility gap at a composition between 40 and 53 mol% ZrO 2 with a monotectic temperature of 1872 ± 7 • C. Moreover, they reported that a subregular ionic solution model best approximates the experimental data. Udalov et al 6,7 also postulated a In comparison to conventional methods, levitation techniques offer decisive advantages for the examination of ceramic melts. The melt is processed without direct contact to a vessel and thus, limitations due to insufficient container material can be omitted.…”
Section: Introductionmentioning
confidence: 99%